2016
DOI: 10.1039/c6cc08038c
|View full text |Cite
|
Sign up to set email alerts
|

Single electron transfer-induced coupling of alkynylzinc reagents with aryl and alkenyl iodides

Abstract: Alkynylzinc reagents were found to undergo coupling with aryl and alkenyl iodides to give arylalkynes and alkenylalkynes without the aid of transition metals. The coupling reaction proceeds through a single electron transfer mechanism, where a substoichiometric amount of a phosphine works as an indispensable activator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…CDCl 3 ): δ = 8.77 (s, 1 H), 8.55 (d, J = 4.0 Hz, 1 H), 7.81 (d, J = 7.8 Hz, 1 H), 7.56-7.54 (m, 2 H), 7.38-7.36 (m, 3 H), 7.30-7.26 (m, 1H); the spectroscopic data are consistent with the literature 19. …”
supporting
confidence: 88%
“…CDCl 3 ): δ = 8.77 (s, 1 H), 8.55 (d, J = 4.0 Hz, 1 H), 7.81 (d, J = 7.8 Hz, 1 H), 7.56-7.54 (m, 2 H), 7.38-7.36 (m, 3 H), 7.30-7.26 (m, 1H); the spectroscopic data are consistent with the literature 19. …”
supporting
confidence: 88%
“…The peak at 3.06 ppm corresponds to the chemical shift of ethynyl protons (peak b), whereas 1.26 ppm and 0.86 ppm (peak *) respectively correspond to the CÀ H chemical shifts of À CH 3 and À CH 2 À , which is the impurity introduced by Et 2 Zn and this is consistent with the impurities in diethylzinc described in the literature. [31] The 1 H NMR spectra of PSA resins synthesized by three different methods are shown in Figure 2. When compared with PSAÀ Zn (seen in Scheme S2 in the Supporting Information), it is evident that the 1 H NMR spectrum of PSA-Et 2 Zn does not have the characteristic peaks at 5.26 ppm, 5.74 ppm, and 6.66 ppm.…”
Section: Structural Characterization Of Psa-et 2 Znmentioning
confidence: 99%
“…[27][28][29][30] Okura et al developed a coupling reaction for alkynylzinc reagents with aryl and alkenyl iodides and without the aid of transition metal catalysis by mixing and heating all the materials including terminal alkynes and Et 2 Zn (in a 2 : 1 ratio). [31] Huang et al reported the first example of Et 2 Zn mediated silylation of 1-aklynes and chlorosilanes and mechanistic studies that support Zn alkynilides as intermediates in the reaction. [32] This reaction protocol comprises a practical method for the preparation of alkynylsilanes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Suzuki–Miyaura coupling, which employs arylboron compounds as arylmetals, is one of the most widely used due to the high stability and high availability of the reagents and the high functional‐group tolerance of the reaction . On the other hand, since our group reported the first electron‐catalyzed cross‐coupling, where aryl Grignard reagents are employed and an electron derived from them instead of a transition metal acts as a catalyst, we and other groups have reported transition‐metal‐free cross‐coupling of arylmetals (Zn/Al/Sn) as well as alkyl‐ and alkynylzinc reagents . Herein, we report for the first time that arylboron compounds can be utilized as aryl nucleophiles in the electron‐catalyzed cross‐coupling with the aid of a zinc reagent such as diethylzinc or zinc chloride/potassium tert ‐butoxide…”
Section: Effect Of the Amounts Of Diethylzinc And Lithium Chloride Inmentioning
confidence: 99%